2016
DOI: 10.1021/acs.joc.6b00991
|View full text |Cite
|
Sign up to set email alerts
|

Formal [3 + 2] Cycloadditions via Indole Activation: A Route to Pyrroloindolines and Furoindolines

Abstract: Here, we describe a novel [3 + 2] cycloaddition of 3-substituted indoles with vinyl aziridines and vinyl epoxides that provides a straightforward approach to pyrroloindolines and furoindolines bearing vinyl groups (up to 96% yield and 9:1 dr). In contrary to previous reports involving Lewis acid activation, this work reports successful reactions based on the activation of indole using t-BuOK and BEt (triethylborane), thereby preserving the free N-H group on indoles. In addition, a gram-scale reaction and a rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Some related studies have also documented the stereoselective construction of structurally diverse polycyclic indoles . In addition, vinyl aziridines, offering a unique combination of reactivity, synthetic flexibility, and atom economy, are multifaceted building blocks for the construction of a number of nitrogen heterocyclics, but few successful examples are known for formation of pyrroloindoline derivatives . In 2017, Hyland et al reported Pd(0)/BPhen complex-catalyzed [3 + 2] cycloaddition for diastereoselective synthesis of racemic 3a-nitropyrroloindolines and cyclopenta­[ b ]­indolines in high yields .…”
Section: Introductionmentioning
confidence: 99%
“…Some related studies have also documented the stereoselective construction of structurally diverse polycyclic indoles . In addition, vinyl aziridines, offering a unique combination of reactivity, synthetic flexibility, and atom economy, are multifaceted building blocks for the construction of a number of nitrogen heterocyclics, but few successful examples are known for formation of pyrroloindoline derivatives . In 2017, Hyland et al reported Pd(0)/BPhen complex-catalyzed [3 + 2] cycloaddition for diastereoselective synthesis of racemic 3a-nitropyrroloindolines and cyclopenta­[ b ]­indolines in high yields .…”
Section: Introductionmentioning
confidence: 99%
“…Many interesting synthetic routes have been developed for this purpose, e.g., [3 + 2] cycloaddition, electrophilic addition/cyclization, cyclopropanation/ring opening/iminium cyclization (CRI reaction), Fischer indolization, copper catalyzed cyclization of iodo-tryptophans and organocatalytic cascade addition-cyclization, etc . Aziridines , have also been exploited for the synthesis of pyrroloindolines .…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] In 2015, Zhao and co-workers developed a formal [3+2] cycloaddition of indole with aziridines to construct tetracyclic hydrocarbazole (Scheme 7). 35 The formal 36 In this reaction, indole 45 was activated with triethylborane and potassium tert-butoxide, and the resulting borate 46 underwent nucleophilic addition at C3 with allylaziridine 47, followed by cyclization to furnish tetracyclic hydrocarbazole 48 in 38% yield with 2:1 dr.…”
Section: [3+2] Cycloadditionmentioning
confidence: 99%